Strength Characteristics of Ternary Mix of Cement in Light Weight Concrete - Vishnu Priya, V; Bhuvaneswari, P; Saravana Raja Mohan, K (International Journal of Engineering and Technology, 2018)
The main aim of this study is to decrease the density and the dead load of the structure by using Light weight concrete (LWC). In this study Pumice aggregate was replaced with the conventional coarse aggregate. To enhance the strength of the concrete, cement was partially replaced with mineral admixtures, Ground Granulated Blast Slag (GGBS) and Metakaolin (MK).Â  The constant replacement level of cement with 30% GGBS and 15% Metakaolin was followed for all the mixes.Â  The natural aggregate has been replaced with pumice from 10% to 50% in the increment of 10%. A total of six combinations were cast. Hardened properties of the concrete were evaluated by conducting compressive strength (100 mm x 100 mm x 100 mm cubes), split tensile strength (cylinder of size 100 mm x 200 mm). In order to enhance the strength properties, cement has been replaced with GGBS and MK at certain replacement levels. The strength properties of light weight concrete samples and the conventional concrete samples were carried out.Â
Keywords: GGBS; Metakaolin; Pumice; Light weight concrete; Strength characteristics.